Application Employee Shift Scheduling Algorithm Recursive Largest First (RLF) at PT. Invilon Sagita Medan - Finus Buulolo; R Mahdalena Simanjorang (Information Technology and Science (ITScience), 2020)
Scheduling is one of the important things in any company such as PT. Invilon sagita currently have employees reaches hundreds of people so that employees who handle scheduling of employees experience difficulty in because of the number of employees is too much. Constraints in the natural is a very long time so it is necessary a method in solving the problem. In this study using Lagert Recusiv First (RLF) in the preparation of Karawan scheduling with visual studio 2010. program based on those already in the test results with the number of employees by 5 people RLF method can resolve employee scheduler quickly.